KESIAPAN KELUARGA DALAM MERAWAT PASIEN PASCA STROKE UNTUK MENINGKATKAN FUNGSI KOGNITIF PASIEN PASCA STROKE DI RUMAH SAKIT UMUM IMLEDA PEKERJA INDONESIA MEDAN - Sarida Surya Manurung; Enggel Dwi Suci Ramadhanti; Abdul Malik Ritonga; Jonni Sastra Manurung; Sheila Hamdah Hanum Ritonga (Jurnal Ilmiah Keperawatan IMELDA, 2026)
Stroke is a neurological disease that can cause physical, emotional, and cognitive impairment in sufferers. Recovery of cognitive function in post-stroke patients requires an active role for the family as the primary caregiver in the rehabilitation process at home. This study aims to explore family readiness in caring for post-stroke patients. The research method used a qualitative approach with a phenomenological design. Data collection was conducted through in-depth interviews with five participants selected using a purposive sampling technique at the Imelda Buruh Indonesia General Hospital in Medan. Data analysis used thematic analysis through a process of coding, categorization, and theme determination. The results of the study identified five main themes, namely: (1) family knowledge about post-stroke patient care, (2) family skills in meeting the patient's basic needs, (3) family readiness in supporting cognitive function recovery, (4) utilization of health services, and (5) barriers to care, such as limited time and emotional burden. The findings indicate that families play an important role in the patient's recovery process, but still face limited knowledge and challenges in implementing optimal care. Therefore, ongoing education and support from health workers are needed to improve family readiness in caring for post-stroke patients at home.